Political institutions as screening devices - Gianluigi Galeotti (Fondazione Eni Enrico Mattei (FEEM), 1997)
The role of private interests in shaping public policies is pervasive both in democratic and non-democratic settings, and the basic task of any political system is that of regulating the market for political influence and sifting out the demands to be satisfied. The paper assumes that collecting and processing information - the hidden information issue materialising the vertical dimension of politics - and selecting interests, the hidden action issue materialising its horizontal dimension, are always dealt with in terms of an ideological syntax (shared goals) and of an institutional architecture (who controls the selection, and how). In analysing those components and their evolution, the paper discusses a number of biases of political screening and considers the main features of the democratic processes in that light. With the fall of information costs, ideology loses its relevance, while the growing competition of interests reduces the space for political collusion. In such a setting, pressure groups can influence policy making only by providing information. A more balanced weighting of opposed interests will eventually emphasise the quasi-judgmental nature of politics.
Keywords: 330